Disrupted student engagement and motivation: observations from online and face-to-face university learning environments - Hari Rajan, Manisha; Herbert, Cristan; Polly, Patsie (Frontiers in Education, 2024)
Student engagement is a crucial factor that can influence both the student learning experience and student success. The return to campus learning and teaching post-pandemic highlighted that many university students are sll adapng to the shi to full-me online learning from hybrid or full-me on-campus learning and are sll experiencing feelings of isolaon, anxiety, and uncertainty. As higher educaon instuons adopt/embed digital methods of teaching and learning with simultaneously moving back to face-to-face learning environments, student feelings of isolaon and disengagement are apparent to educators. This 'transion' in our opinion, has impacted how learners engage in digital as well as face-to-face environments. Previous studies have highlighted the importance of engagement within an online seng as it brings about new factors for student learning and teaching that were not fully considered before. To address this issue, universies have sharpened the focus on improving student movaon, self-efficacy, and their sense of belonging within their learning community. As educators, it is important for us to understand this period of student disengagement and develop strategies to overcome and support students. We can acknowledge that such challenges are likely to resurface in the future, therefore it is essenal that we are able to provide frameworks to enhance student engagement within higher educaon. We believe that in creang an effecve learning environment, whether it be online or on-campus, educators need to develop intrinsic movaon techniques and collaborave spaces to increase the sense of belonging for students and improve their overall engagement with their learning course content.